PENDIDIKAN ISLAM DALAM PERSPEKTIF FILSAFAT ILMU - Mohammad Muslih (Hunafa: Jurnal Studia Islamika, 2011)
Abstract: The process and the scintifc result will depend on their philosophical bases, covering theoretical framework, scientifc paradigm and basic assumption. The three bases become the philosophical base that function to allot framework, direction and scientific colour  that will be produced. The Islamic wordview in the perspective of  the philospy of science basically serves as the theological-methaphisical assumntion or hard core in the scientifc field of the Islamic eduation. It is the special characteristic that makes it different from the secular education. Employing this kind of paradigm, the Islamic education will be able to identify the difference between proselytazing approach from scientific approach.Kata Kunci: pendidikan Islam, filsafat ilmu, teologis metafisis, paradigma